Pengaruh Strategi Interactive Learning dan Minat Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak di MTs Makrifatul Ilmi Bengkulu Selatan - Mona Nopitasari; Suhirman Suhirman; Nurlaili Nurlaili (UIN Fatmawati Sukarno Bengkulu, 2025)
The objectives of this research are 1). To determine the effect of interactive learning strategies on student learning outcomes in the subject of moral beliefs in class VIII MTs Makrifatul Ilmi South Bengkulu. 2). To determine the influence of interest in learning on student learning outcomes in the subject of moral beliefs in class VIII MTs Makrifatul Ilmi South Bengkulu. 3). To determine the influence of interactive learning strategies and interest in learning on student learning outcomes in the subject of moral beliefs in class VIII MTs Makrifatul Ilmi South Bengkulu. This type of research is quantitative research with an associative approach. Data collection using questionnaires and documentation. The results of this research are 1). There is a significant influence between the application of Interactive Learning Strategies on student learning outcomes in the subject of moral beliefs in class VIII MTs Makrifatul Ilmi South Bengkulu amounting to 2.765 with a level of influence of 27.4%. 2). There is a significant influence between interest in learning on student learning outcomes in the Aqidah Akhlak subject in class VIII MTs Makrifatul Ilmi South Bengkulu amounting to 3.182 with an influence level of 45.1%. 3). There is a significant influence between the application of Interactive Learning Strategies and interest in learning simultaneously on student learning outcomes in the Aqidah Akhlak subject in class VIII MTs Makrifatul Ilmi South Bengkulu amounting to 13,408 with an influence level of 35.8%.